PENINGKATAN INOVASI GURU MELALUI PENGUATAN LITERASI INFORMASI DAN EFIKASI DIRI - Ika Yanti Sholihah; Soewarto Hardhienata; Eka Suhardi (JURNAL MANAJEMEN PENDIDIKAN, 2021)
INCREASING TEACHER INNOVATION THROUGH STRENGTHENING INFORMATION LITERACY AND SELF-EFFICIENCYTeacher innovation is closely related with new knowledge, methods and strategies as well as learning service. Those aspects are very important to support the achievement of national education as well. This study aimed to find out that there was a relationship between teacher innovation increase with information literacy and self-efficacy strength. This research was conducted with a quantitative approach using correlation analysis and SITOREM analysis. The research was carried out in 7 public high schools around Cibinong, Bogor Regency. The population of the study was 178 civil servant teachers. The results of the study as the following conclusions: 1) there was a positive and significant relationship between information literacy and teacher innovation (ry1 = 0.662), 2) there was a positive and significant relationship between self-efficacy and teacher innovation (ry2 = 0.643), 3) there was a positive relationship between information literacy and self-efficacy together with teacher innovation (ry12 = 0.801). The efforts that need to be improved in order to increase teacher innovation are; 1). utilization of information to solve problems, 2) introduction of required information, 3) commitment to goals, 4) creating new ideas in learning, 5) optimizing learning services, 6) developing ICT, 7) improving/renewing ideas in learning.